Work Environment, Leadership, and Culture as Drivers of Employee Performance: The Mediating Role of Work Engagement - Karami, Muhammad Radifan; Kusiyah, Kusiyah (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study examines the effects of the work environment, leadership style, and organizational culture on employee performance, with work engagement as a mediating variable, at PT Mayasari Bakti. A quantitative survey design was applied to 441 employees/drivers selected through stratified proportional random sampling. Data were collected via a Google Forms questionnaire and analyzed using PLS-SEM with SmartPLS. The findings show that the work environment (β = 0.32, p < 0.05) and organizational culture (β = 0.41, p < 0.05) have significant positive effects on work engagement, whereas leadership style has no significant effect. Work engagement significantly influences employee performance (β = 0.47, p < 0.05). Moreover, the work environment and organizational culture do not directly affect employee performance but have significant indirect effects through work engagement, indicating full mediation. Leadership style shows neither direct nor indirect effects on performance. These results highlight the importance of fostering employee engagement through supportive work conditions and a strong organizational culture to enhance performance, particularly in labor-intensive transportation and service organizations. The study is limited by its cross-sectional design and single-organization scope, which may limit causal inference and generalizability.